Albert Camus et la démocratie comme alternative aux totalitarismes du xxe siècle - Emanuela Celotto (Carnets)
This article proposes a (re)reading of Camus creation from the perspective of the democracy in order to demonstrate the innovative aspect of his thought, which is more actual than ever. After outlining a portrait of the author as a committed journalist, we will proceed to a comparative analysis between Camus and intellectuals who influences his democratic thought and inspired his thinking on totalitarianism. Then, based on a selection of works, we will examine the technique adopted by Camus to transfer into the fictional the democratic debate against totalitarianism of his era. Finally, we will study from a lexicological point of view the terms of totalitarianism and democracy, and their synonyms within the semantic field of the antitotalitarian debate.